Decay resistance, thermal degradation, tensile and flexural properties of sisal carbon hybrid composites - Tufan, Mürşit; Akbaş, Selçuk; Aslan, Mustafa (Maderas. Ciencia y Tecnología, 2016)
Sisal-carbon hybrid composites were produced from mixtures having different weight ratios of sisal, carbon fibers and recycled polypropylene. All formulations were tested and evaluated for tensile and flexural properties. In addition, the thermal stability of the sisal-carbon hybrid composites were examined via thermogravimetric analysis and decay tests were conducted to determine the degradation of the hybrid composites. Results showed that the biological durability and mechanical and thermal properties improved with the increasing weight ratios of carbon fiber in the hybrid composites. According to the mechanical tests, the optimum hybrid composite formulation was found to be 12% sisal fiber + 28% carbon fiber + 60% rPP.